Effect of polyfluoroalkyl chemicals on the occurrence of urge urinary incontinence: a population-based study. (July 2021) - Cui, Shu; Zhao, Xinghua; Chu, Xiaohan; Zhang, Shengwei; Gu, Qingyang; Xu, Changbao
Background: The artificial fluorinated group of compounds polyfluoroalkyl chemicals (PFCs) has been applied extensively in daily life for decades, and is present in food, drinking water, and indoor dust. The nephrotoxicity of PFCs has been widely studied for its characteristics of being mainly excreted through passing urine and affecting urodynamics. This work aimed to investigate the relationship between PFCs and the occurrence of urge urinary incontinence (UUI) in the United States (US) population. Methods: There were 3157 eligible female participants retrieved from the National Health and Nutrition Examination Survey (NHANES) between 2007 and 2014. A logistic regression model was used to examine the relationship between UUI and eight kinds of PFCs. The dose–response relationship was investigated through restricted cubic spline analysis in this retrospective study. Results: Of the 3157 eligible female participants, 913 self-reported a history of UUI. Total PFCs, perfluorohexane sulfonic acid (PFHS), 2-(N-methyl-perfluorooctane sulfonamido) acetate (MPAH), and perfluorononanoic acid (PFNA) correlated positively with the occurrence of UUI after adjusting for age, race, education, vigorous recreational activities, hypertension, diabetes, body mass index (BMI), creatinine, and estimated glomerular filtration rate (eGFR). Based on the results of sub-group analysis, the increasing tertiles contained odds ratios [OR; 95% confidence intervals (CI)] of 1.25 (95% CI, 1.03–1.51, p  = 0.026) and 1.56 (95% CI, 1.29–1.89, p  < 0.001) for total PFCs compared with the lowest tertile. The OR for PFHS, MPAH, and PFNA were 1.75, 1.71, and 1.41 respectively, in the highest tertile. Conclusion: This study investigated the relationship between PFCs and UUI in female and found total PFCs, PFHS, MPAH, and PFNA were positively correlated with the risk of UUI. The results will contribute to developing individualized treatment for female patients suffering UUI.